Seasonal assessment of the structural and functional potential of microbial communities in a full-scale treatment wetland for combined sewer overflows - Katharina Tondera; Sarah J. Wallace; Jan Ruppelt; Mark Button; Kela P. Weber (Ecological Engineering, 2026)

Rheological characterization and modeling of freshwater and marine microalgae and cyanobacteria mixed cultures - Conor Button; Nature Poddar; Tom Lacassagne; Mathieu Pernice; Vishal Gupta; Lisa Aditya; Unnikrishnan Kuzhiumparambil; Peter J. Ralph (Algal Research, 2025)

Washover fan deposits resulting from perigean spring tides: An example from Cape Cod, Massachusetts, USA - Katherine A. Castagno; Eliza J. Fitzgerald; Kaitlyn Button; Petra Zuñiga; Tommy Tucker; Timothy Smith; Mark Borrelli (Geomorphology, 2025)

Editorial: The society for environmental geochemistry and health (SEGH): 50 years and beyond - M. J. Watts; A. Argyraki; M. Barbieri; A. Brown; M. Button; R. Finkelman; G. Gibson; O. Humphrey; X. Huo; A. S. Hursthouse; B. Kaninga; P. Marinho Reis; et al. (Environmental Geochemistry and Health, 2023)
When the SEGH international board released a short editorial paper back in 2019, we described an aim to increase the membership offering, whilst improving the diversity of input regionally, by scientific discipline and to ensure greater and more regular contact across the regions from 2020 onwards. Wider aspirations described in 2019 (Watts et al. 2019) are discussed within this short communication at the end of 2021 to evaluate progress made. In particular, how the SEGH community adapted to the unprecedented circumstances that have challenged each and every one of us throughout the COVID-19 pandemic since early 2020 and are likely to influence our activities for the foreseeable future.

Endurance-exercise training adaptations in spinal motoneurones: potential functional relevance to locomotor output and assessment in humans - Kevin E. Power; Evan J. Lockyer; Alberto Botter; Taian Vieira; Duane C. Button (European Journal of Applied Physiology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Arsenic speciation in the bracket fungus Fomitopsis betulina from contaminated and pristine sites - Mark Button; Iris Koch; Michael J. Watts; Kenneth J. Reimer (Environmental Geochemistry and Health, 2020)

The Society for Environmental Geochemistry and Health (SEGH): building for the future - Michael J. Watts; Taicheng An; Ariadne Argyraki; Emmanuel Arhin; Anthea Brown; Mark Button; Jane A. Entwistle; Robert Finkelman; Gillian Gibson; Olivier S. Humphrey; Xia Huo; Andrew S. Hursthouse; et al. (Environmental Geochemistry and Health, 2020)

Short-interval intracortical inhibition of the biceps brachii in chronic-resistance versus non-resistance-trained individuals - Behzad Lahouti; Evan J. Lockyer; Shawn Wiseman; Kevin E. Power; Duane C. Button (Experimental Brain Research, 2019)

Short-interval intracortical inhibition to the biceps brachii is present during arm cycling but is not different than a position- and intensity-matched tonic contraction - L. R. Alcock; A. J. Spence; E. J. Lockyer; D. C. Button; Kevin E. Power (Experimental Brain Research, 2019)

Investigating the Complex Association Between Viral Ecology, Environment, and Northeast Pacific Sea Star Wasting - Ian Hewson; Kalia S. I. Bistolas; Eva M. Quijano Cardé; Jason B. Button; Parker J. Foster; Jacob M. Flanzenbaum; Jan Kocian; Chaunte K. Lewis (Frontiers in Marine Science, 2018)

Arsenic speciation in polychaetes (Annelida) and sediments from the intertidal mudflat of Sundarban mangrove wetland, India - M. J. Watts; T. S. Barlow; M. Button; S. K. Sarkar; B. D. Bhattacharya; Md. Aftab Alam; A. Gomes (Environmental Geochemistry and Health, 2013)

Cranial biomechanics of Diplodocus (Dinosauria, Sauropoda): testing hypotheses of feeding behaviour in an extinct megaherbivore - Mark T. Young; Emily J. Rayfield; Casey M. Holliday; Lawrence M. Witmer; David J. Button; Paul Upchurch; Paul M. Barrett (The Science of Nature, 2012)

Delayed onset of seizures and toxicity associated with recreational use of Bromo-dragonFLY - David M. Wood; Jemma J. Looker; Loua Shaikh; Jenny Button; Malgorzata Puchnarewicz; Susannah Davies; Satnam Lidder; John Ramsey; David W. Holt; Paul I. Dargan (Journal of Medical Toxicology, 2009)

Physical analysis of the complex rye (Secale cereale L.) Alt4 aluminium (aluminum) tolerance locus using a whole-genome BAC library of rye cv. Blanco - B.-J. Shi; J. P. Gustafson; J. Button; J. Miyazaki; M. Pallotta; N. Gustafson; H. Zhou; P. Langridge; N. C. Collins (Theoretical and Applied Genetics, 2009)

Earthworms and in vitro physiologically-based extraction tests: complementary tools for a holistic approach towards understanding risk at arsenic-contaminated sites - Mark Button; Michael J. Watts; Mark R. Cave; Chris F. Harrington; Gawen T. Jenkin (Environmental Geochemistry and Health, 2009)

Effect of environmental toxicants on enzyme biosynthesis: A comparison of ?-galaclosidase, ?-glucosidase and tryptophanase - Ronald J. Button; Gabriel Bitton; Ben Koopman; Orna Agami (Archives of Environmental Contamination and Toxicology, 1990)